Discussions on Subgraph Ranking for Keyworded Search - Song, Justin J.; Kang, Inkyo; Lee, Wookey; Kim, Jinho; Lee, Joo Yeon (Proceedings - IEEE 2018 International Congress on Cybermatics: 2018 IEEE Conferences on Internet of Things, Green Computing and Communications, Cyber, Physical and Social Computing, Smart Data, Blockchain, Computer and Information Technology, iThings/GreenCom/CPSCom/SmartData/Blockchain/CIT 2018, 2018)
Recently many graph information can be available in numerous application domains, including relational database s, Web, Bioinformatics, Chemistry reaction information, Ontol ogy, XML, Social Networks, Patent Information, Paper citatio n, and RDF graphs, etc. Graphs also have structure to be foun d to express complicate data relationships like Web, Database, XML Document and Semantic Web. Traditionally, user had to learn difficult query languages like SQL to do information sear ch over graph structures. There are needs to find out a simple and effective keyword search method for non-Technical users so as to use a keyword search method on the ever-increasing gra ph data. The purpose of this research is to develop a method fo r ranking over the graph structures. We propose the relevance score for each node and link by using each query keyword.
Keywords: Data relationships; Graph information; Graph structures; Keyword search; Non-technical users; Patent information; Relational Database; Relevance score